Evaluation of sustainable livelihood of reservoir resettlement based on the fuzzy matter-element model - Hao, Yu; Zhang, Fan; Sun, Chaolun (Frontiers in Environmental Science, 2023)
The study of sustainable livelihoods for reservoir resettlers is of great significance for consolidating the poverty alleviation achievements of China and promoting the realization of the major strategy of China's rural revitalization. On the basis of the Sustainable Livelihood Analysis Framework of the UK Agency for International Development and the general requirements of the rural revitalization strategy on industry, ecology, rural ethos, governance and life, this paper selects the material basis, living environment and Social Adaptability which are more close to China's national conditions and can more accurately measure the resettlers' livelihood. These three factors have established a Comprehensive Evaluation Index System for the sustainable livelihood of the reservoir resettlers. A mathematical model based on complex fuzzy matter-element and analytic hierarchy process (AHP) is established to assess the sustainable livelihood of reservoir resettlers. Furthermore, it conducts an empirical study on the resettlement of the Danjiangkou Henan Reservoir area of the South-to-North Water Diversion Project, which takes the whole of immigration in Henan Province as the research object. The results show that the current survey value of the overall livelihood of the resettlers in the Danjiangkou Henan Reservoir Area of the South-to-North Water Diversion Project is 0.0085 lower than the maintaining livelihood target and 0.1725 lower than the sustainable livelihood target. Such a result indicates that the livelihood of Henan resettlers in the Danjiangkou Henan Reservoir Area of the South-to-North Water Diversion Project has reached a sustainable level overall, but its gap with the sustainable livelihood goal remains obvious, which is primarily demonstrated by economic foundation and social adaptability. Therefore, immigration management agencies should make efforts to adjust the industrial structure, increase the income of resettlers, help resettlers integrate into the local society sooner, and promote the sustainable development of resettlers' livelihoods.